Effects of Pretreatments on the Shelf Life and Quality of Carrots (Daucus carota Subspecies Sativus) Stored at Different Temperatures - Omolara Ojuolape Adeoye; Tinuola Tokunbo Adebolu; Muftau Kolawole Oladunmoye; Anthony O. Ojokoh (Archives of Current Research International, 2019)
Carrot is one of the top ten most important vegetables in the world due to its nutritional contents however, it is highly perishable. One major way to extend its shelf life is to store in the refrigerator but these can only prolong the shelf life for only a few weeks. Therefore, there is the need to research how the shelf life can be extended further. Fresh matured carrots bought from Shasha market in Akure, Ondo State, Nigeria were washed with potable water and grouped into 7; each group was subjected to different pretreatment except the 7th group that was left untreated. All the carrot groups were dried in sun for five hours and then packed aseptically into different sterile air tight polyethylene food bags. Each group was replicated and one batch was stored in the refrigerator (4 ± 2°C) while the other batch was stored at room temperature (30 ± 2°C). At intervals of one week, the samples were monitored for presence of soft rot, wrinkle, weight loss etc. All carrots stored at 30 ± 2°C got spoiled after first week of storage irrespective of the type of pretreatment they were subjected to. However, pretreated carrots stored at 4 ± 2°C had their shelf life extended with those treated with moringa seed aqueous extract having the best result at 24th week. This work shows that moringa seed aqueous extract can be used to extend the shelf life of carrots stored in the refrigerator.